Lost in delegation? (Dis)organizing for sustainability. Issue 1 (March 2018) - Allen, Stephen; Brigham, Martin; Marshall, Judi
Highlights: An approach is developed for exploring sociomaterial interdependencies in organizational transformations for sustainability. Actor-network approaches are developed with the concept of localised hybridity and by showing the importance of reflexivity. Sustainability visions require reflexive attention to the relational work involved in forming alliances with mediators. Abstract: Using actor-networks as our conceptual lens for appreciating complex sociomaterial interdependencies, we explore how a vision to "do things differently" for sustainability becomes enacted and significantly diluted at a major brownfield development project in the UK. We show how visions for sustainability can become substantially delegated into a range of specialised and functionally differentiated practices, with nonhuman mediators producing significant agency. Additionally, extending actor-network approaches, we develop the concept of localised hybridity to consider how the possibilities for progressive sustainability practices are interdependent with mediators in other 'locals' across times and spaces. We suggest that greater reflexive attention and inquiry to the types of relational work required to form alliances with nonhuman mediators is crucial to realise visions for sustainability.